Negotiating Authenticity: Reproducing the Past for the Present - (:unkn) unknown (My University, 2023)
Negotiating Authenticity: Reproducing the Past for the Present explores how reproductions connect us to the past. From Rembrandt restrikes to plastic souvenirs, reproductions occupy an important chapter in an object’s biography. This exhibition considers the complex relationships between "original” artifacts and their reproductions, which historically has been the focus of scholarly debate. Walter Benjamin, in his 1936 essay The Work of Art in the Age of Technological Reproduction, highlights the intrinsic questions posed of this relationship – when an original work of art (or object) is reproduced, what relationship does both the reproduction and its model (the original) have with each other as well as the past, people, and places they represent? By utilizing reproductions to engage two foundational approaches to understanding authenticity – the materialist, which emphasizes the importance of inherent and measurable traits in determining an object’s authenticity, and the constructivist, which emphasizes the importance of context and the social networks in determining an object’s authenticity – Negotiating Authenticity challenges the materialist/constructivist dichotomy and highlights the complex and convoluted ways objects and their reproductions help us form connections between the past and the present.
Keywords: Authenticity; Material Culture; Pastness; Reproductions